Fern species diversity across various land use types of Mt. Makiling, Luzon Island, Philippines - Ailene Antonio Alcala; Marjorie D Delos Angeles; Inocencio, Jr. E Buot (Society for Indonesian Biodiversity, 2019)
Abstract. Alcala AA, Delos Angeles MD, Buot Jr IE. 2019. Fern species diversity across various land use types of Mt. Makiling, Luzon Island, Philippines. Biodiversitas 20: 2437-2445. Mt. Makiling of Luzon Island, Philippines is home to many living organisms including ferns and fern allies which are one of the important understory vegetation in many forest communities and having various economic uses like food, medicine and ornamentation. This study identified fern species found in various land use types across the northeastern slope of Mt. Makiling, Los Baños, Philippines. The plot technique was employed using a 20x20 meter quadrat. Three (3) 5x2 subquadrats were randomly distributed within the established quadrat. Fern specimens were identified (sensu PPG, 2016) and measured. Samples were collected for herbarium voucher deposited in the PBDH. A total of 28 fern species with 22 genera from 14 families were found across land use types. Identified land use types were: i) Mahogany (341 m asl.); (ii) Agriculture (355 m asl.); (iii) Buffer zone (365 m asl.); (iv) Agroforest (368 m asl.); (v) Roadside (455 m asl.), and (vi) Forest (482 m asl.). The most represented fern families were found out to be Thelypteridaceae (5 spp), Dryopteridaceae (3 spp), Polypodiaceae (3 spp.), Pteridaceae (3 spp), Aspleniaceae (2 spp), Dennstaedtiaceae (2 spp), Selaginellaceae (2 spp.) and Tectariaceae (2 spp.). On the other hand the families Schizaeaceae, Lindsaeaceae, Davalliaceae, Nephrolepidaceae, and Marratiaceae are comprised of one species only. Pteris blumeana C. Agardh and Tectaria crenata Cav. were found only in buffer zone area. Dennstaedtia philippinensis Copel., Lygodium circinnatum (Burm. f.) Sw. and Microlepia sp., were found only in agroforest area; Sphaerostephanos unitus (L.) Holttum found only in agricultural; Bolbitis heteroclita (C. Presl) Ching and Microsorum membranifolium (R. Br.) Ching were found in roadside while Asplenium tenerum G. Forst. , Christella sp., Lindsaea fissa Copel. and Nephrolepis cordifolia (L.) C. Presl were found in forest area. Pneumatopteris nitidula (C. Presl) Holttum. is a dominant fern species found in agriculture and mahogany plantation area. There is a need to document fern species along with its population across land use types in order to utilize ferns as plant indicators due to their vulnerability to changes in environmental conditions. These results can shed light on the appropriate strategy for the conservation and management of ferns in Mt. Makiling.